2021
DOI: 10.3389/fsurg.2021.715083
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Laparoscopic vs. Open Pancreaticoduodenectomy After Learning Curve: A Systematic Review and Meta-Analysis of Single-Center Studies

Abstract: Background: Although laparoscopic pancreaticoduodenectomy (LPD) is a safe and feasible treatment compared with open pancreaticoduodenectomy (OPD), surgeons need a relatively long training time to become technically proficient in this complex procedure. In addition, the incidence of complications and mortality of LPD will be significantly higher than that of OPD in the initial stage. This meta-analysis aimed to compare the safety and overall effect of LPD to OPD after learning curve based on eligible large-scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…[13] reported a postoperative complication rate of 37.2%, which is not different from 35.7% reported in our study. Besides, LPD is associated with fast recovery and shorter postoperative hospital stay days compared to OPD [10] . The postoperative hospital stay days in our analysis was 17 (13,24) days, which is consistent with 18.6 ± 5.6 days in previous data by Cheng, J. F. [14] .…”
Section: Lpd Vs Opdmentioning
confidence: 98%
See 1 more Smart Citation
“…[13] reported a postoperative complication rate of 37.2%, which is not different from 35.7% reported in our study. Besides, LPD is associated with fast recovery and shorter postoperative hospital stay days compared to OPD [10] . The postoperative hospital stay days in our analysis was 17 (13,24) days, which is consistent with 18.6 ± 5.6 days in previous data by Cheng, J. F. [14] .…”
Section: Lpd Vs Opdmentioning
confidence: 98%
“…Comparison of OPD with LPD showed that LPD leads to less bleeding and lower transfusion rate than OPD due to the magni cation of the eld of view by laparoscopy [9,10] . Our study showed that intraoperative blood loss was 200 (200, 400) ml, ndings that were comparable to a previous study which showed intraoperative blood loss of 350 (290-450) ml [11] .…”
Section: Lpd Vs Opdmentioning
confidence: 99%
“…The development of technology and minimally invasive tendency in medicine and minimally invasive pancreaticoduodenectomy, especially total laparoscopic pancreaticoduodenectomy (tLPD), is not out of this way. Recent systematic reviews showed that LPD was superior against open PD in aspects of inoperative blood transfusion, wound and pulmonary infection, and shorter hospital stays, and there are no differences of relevant postoperative pancreatic fistula (POPF), severe complications, postoperative mortality, retrieved lymph nodes (LNs), and R0 resection rate [3,4]. However, to achieve the safety and effectiveness, they also recommended that LPD should be done by surgeons with expertise and through learning curve in high-volume centers [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Since PD surgery requires the removal of several organs and complex anatomical relationships, as well as reconstruction of the digestive tract, the early postoperative mortality rate is 20-30%. In recent years, with the rapid development of surgical techniques and careful planning of the perioperative period, the mortality rate has decreased to less than 5% [1], but the postoperative complication rate remains relatively high [2][3][4], so PD is one of the most complicated procedures in abdominal surgery. Therefore, surgeons need to do early accurate diagnosis for such tumors, make clear the situation, such as the size the shape and adjacent organs of the tumor, whether the surrounding vascular system was invaded by the tumor, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 1. Relationship between tumor and artery,2 Relationship between tumor and vein,3 Relationship between tumor and portal vein,4 Distribution of lymph nodes (green is suspected lymph node).Surg. Tech.…”
mentioning
confidence: 99%